2023
DOI: 10.1007/s00445-023-01669-6
|View full text |Cite
|
Sign up to set email alerts
|

The influence of heterogeneity on the strength of volcanic rocks and the stability of lava domes

Michael J. Heap,
Claire E. Harnett,
Tofig Nazarbayov
et al.

Abstract: The collapse of lava domes, inherently heterogeneous structures, represents a significant volcanic hazard.Numerical and analogue models designed to model dome instability and collapse have incorporated heterogeneity 2 in the form of discrete zones with homogeneous properties. Based on an assessment of dome rock heterogeneity, we explore whether material property heterogeneity ("diffuse" heterogeneity) within these discrete zones can promote dome instability. X-ray computed tomography shows that dome samples ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 101 publications
0
0
0
Order By: Relevance
“…PFC has been previously used to successfully model the mechanical behaviour of rock (e.g., Potyondy and Cundall, 2004) and, recently, to model dome growth and collapse (Husain et al, 2014(Husain et al, , 2018Harnett et al, 2018;Husain et al, 2019;Harnett and Heap, 2021;Walter et al, 2022;Heap et al, 2023a). These DEM models consider a particlebased material in which circular particles interact at interparticle contacts.…”
Section: Numerical Modellingmentioning
confidence: 99%
See 1 more Smart Citation
“…PFC has been previously used to successfully model the mechanical behaviour of rock (e.g., Potyondy and Cundall, 2004) and, recently, to model dome growth and collapse (Husain et al, 2014(Husain et al, , 2018Harnett et al, 2018;Husain et al, 2019;Harnett and Heap, 2021;Walter et al, 2022;Heap et al, 2023a). These DEM models consider a particlebased material in which circular particles interact at interparticle contacts.…”
Section: Numerical Modellingmentioning
confidence: 99%
“…Second, modelling has shown that the mechanical properties of dome-and edifice-forming rock plays a first-order role in dictating their stability and therefore the risk of collapse and associated hazards (Apuani et al, 2005;Reid et al, 2001;Moon et al, 2009;Borselli et al, 2011;Schaefer et al, 2013;Heap et al, 2021a, b;Harnett and Heap, 2021;Wallace et al, 2022;Mordensky et al, 2022;Harnett et al, 2022;Carr et al, 2022;Heap et al, 2023a) and so, if water-saturation reduces rock strength, it must also decrease dome and edifice stability.…”
Section: Introductionmentioning
confidence: 99%